2002
DOI: 10.1007/bf03345080
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and intellectual development of children of mothers taking methimazole during pregnancy

Abstract: There is some debate regarding the safety of methimazole (MMI) therapy during pregnancy. It is not known whether MMI therapy in mothers during pregnancy is safe for their children or if it causes alterations in thyroid function and intellectual development during childhood. Twenty-three children, whose mothers were hyperthyroid during pregnancy and treated with MMI 5-20 mg were studied from age 3-11 yr. Thyroid function and liver function tests, urinary iodine, anti-thyroid antibodies, intelligence quotient (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Effect on pediatric physical and mental growth No differences in thyroid function or physical and psychomotor development has been found between children born to MMI-or PTU-treated hyperthyroid mothers during pregnancy and those born to euthyroid mothers (43,44).…”
Section: What Are the Associated Complications With Antithyroid Drugsmentioning
confidence: 98%
“…Effect on pediatric physical and mental growth No differences in thyroid function or physical and psychomotor development has been found between children born to MMI-or PTU-treated hyperthyroid mothers during pregnancy and those born to euthyroid mothers (43,44).…”
Section: What Are the Associated Complications With Antithyroid Drugsmentioning
confidence: 98%
“…However, no increase in frequency of congenital anomalies in infants exposed to methimazole in utero have been reported by others [84], and at least one case of chronal atresia has been reported in a newborn exposed to propylthiouracil [85]. Studies have shown that school-aged children who were exposed to thionamides, in particular methimazole, during intrauterine life have normal thyroid function and physical and intellectual development [86][87][88].…”
Section: Pregnancymentioning
confidence: 95%
“…Total IQ for the methimazole-treated group was 11711; IQ for the control group was 11314. The authors concluded that no detrimental effects on the physical or intellectual development occurred in those children exposed to methimazole during pregnancy (Azizi, 2002). The main strength of this study was the single blinded psychologist evaluation of child intellect using the WPPSI exam.…”
Section: Wwwintechopencommentioning
confidence: 97%
“…Azizi et al evaluated the methimazole's effect on intellectual development of children whose mothers received methimazole during pregnancy but not during lactation (Azizi, 2002). The authors identified 23 children, ages 3 to 11 years, of mothers who were treated with methimazole during pregnancy and 30 children, ages 3 to 11 years, of mothers who were not treated with methimazole during pregnancy.…”
Section: Wwwintechopencommentioning
confidence: 99%